Water purification using different waste fruit cortexes for the removal of heavy metals. Issue 5 (1st September 2016) - Al-Qahtani, Khairia M.
Abstract: The use of different cortex fruit wastes, including banana, kiwi and tangerine peels, for removing toxic and heavy element Cd +2, Cr +3 and Zn +2 ions from aqueous solutions has been previously investigated. The ground material was powdered in a mortar and passed through a screen to obtain two different particle sizes, 1 and 2 mm, for all of the powders. In preliminary experiments using kiwi cortex, material with a 1-mm particle size showed a higher retention capability (up to 10–16% of Cd +2, Zn +2 and Cr +3 ) than material with 2-mm particles. Considering these results, material with a 1-mm particle size was used in further experiments with the other waste materials. For Cd +2, Zn +2 and Cr +3 removal, it was determined that kiwi and tangerine cortex showed better biosorption capability when compared with banana cortex (up to 35% more for Cd, 25% more for Zn and 35% more for Cr). The effects of the initial concentration (10–100 mg/l), pH (2–10), adsorbent dosage (0.1–2.0 g) and contact time (5–120 min) were studied at room temperature. A strong dependence of the adsorption capacity on the initial metal concentration was observed. The capacity increased as the initial concentrations decreased. A maximum removal was observed at an adsorbent dosage of 2.0 g and an initial concentration of 10 mg/l. The adsorption isotherms of the different cortex fruit wastes were determined. The equilibrium data were tested using a Langmuir isotherm model, and the kinetics conformed to the pseudo-second equation. The order of the maximum adsorption capacity of these metal ions on banana was Cr +3  < Cd +2  < Zn +2, whereas it was Cd +2  < Cr +3  < Zn +2 for kiwi and tangerine. Complexation is proposed as the adsorption mechanism. The experimental results show that the natural biosorbent was effective for the removal of pollutants from an aqueous solution.